Analisis Pemasaran Jeruk Siam di Desa Poncokusumo Kabupaten Malang - Sintia, Bella; Widodo, Wahyu; Sutawi, Sutawi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Siamese oranges are one of the horticultural crops that have a myriad of advantages that have business opportunities. The objectives of this study are 1. to determine the marketing channel of chayote in Poncokusumo from farmers to retailers, 2. to identify the amount of production costs, marketing margins, marketing profits, farmer share, marketing efficiency of chayote in Poncokususmo. This research was conducted in Poncokusumo Village, Poncokusumo District, Malang Regency in July 2023. Data analysis used in this study is quantitative descriptive analysis. The results of research on the marketing channel of siam oranges in Poncokusuma village there are 2 channels, namely Channel I: Farmers - Middlemen - Wholesalers - Retailers - Consumers and Channel II: Farmers - Wholesalers - Retailers - Consumers. The highest average income is Rp.653,437,074, R/C ratio 11.5 with production of 47,708 Kg/Ha. Marketing efficiency of channel II is 7% very efficient. The conclusion is that shorter marketing channels result in smaller marketing margins, more efficient marketing costs, and farmers receive higher selling prices.